1997
DOI: 10.1590/s0004-282x1997000500011
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for recurrence of a first seizure during childhood

Abstract: This study was designed with the objective of evaluating the chance of recurrence in our area and to answer questions regarding prognostic factors capable of helping in the management of the first seizure in childhood. One hundred and thirty six children from 1 month to 12 years of age seen at the Pediatric Emergency Division of Hospital de Clínicas de Porto Alegre because of a first seizure with or without triggering factors were included in the study. The follow-up included 121 children. We concluded that fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Although convulsive seizures represent a relatively common cause of admission to the PED, recent epidemiological studies on first‐ever epileptic seizures in children in this setting are lacking, especially encompassing all the different key aspects of the phenomenon, including frequency and aetiology of the first seizure, risk of recurrence, and of receiving a diagnosis of epilepsy. The two most comprehensive studies in this respect, most similar to our work, and focusing on epidemiological data and the risk of recurrence in children after the first seizure, including both ‘unprovoked’ and ‘provoked’ aetiologies, date back over 20 years . A third, similarly comprehensive study was performed more recently in Taiwan, although, it should be noted, in a socio‐economic setting very different to ours …”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although convulsive seizures represent a relatively common cause of admission to the PED, recent epidemiological studies on first‐ever epileptic seizures in children in this setting are lacking, especially encompassing all the different key aspects of the phenomenon, including frequency and aetiology of the first seizure, risk of recurrence, and of receiving a diagnosis of epilepsy. The two most comprehensive studies in this respect, most similar to our work, and focusing on epidemiological data and the risk of recurrence in children after the first seizure, including both ‘unprovoked’ and ‘provoked’ aetiologies, date back over 20 years . A third, similarly comprehensive study was performed more recently in Taiwan, although, it should be noted, in a socio‐economic setting very different to ours …”
Section: Discussionmentioning
confidence: 58%
“…The two most comprehensive studies in this respect, most similar to our work, and focusing on epidemiological data and the risk of recurrence in children after the first seizure, including both 'unprovoked' and 'provoked' aetiologies, date back over 20 years. 5,18 A third, similarly comprehensive study was performed more recently in Taiwan, although, it should be noted, in a socio-economic setting very different to ours. 1 The main body of available published research to date has focused on subgroups of patients, in particular on the subset of 'unprovoked seizures' which, although representing an important diagnostic challenge, do not represent the main cause of PED visits for seizures.…”
Section: Discussionmentioning
confidence: 74%
“…Most publications regarding childhood epilepsy report a clear predominance of cases affecting males 25 , especially between the ages of 5 and 10. This is also valid for BRE cases, which affects boys and girls 5 in a proportion of 6:4 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The first unprovoked seizure is always devastating and frightening events for the parents so it is very crucial to make a rational decision whether treatment should be started or not after a first unprovoked seizure. Age of onset of first seizure, gender, positive family history, perinatal history, seizure type, EEG result all these factors have shown an association with recurrences from various studies, but they still remain inconclusive [6], [7]. Majorities of study have been shown epileptiform discharge in electroencephalogram (EEG) and remote symptomatic seizure as main factors for recurrences [8], [9].…”
Section: Introductionmentioning
confidence: 99%